LANGUAGE AND CULTURE: THEIR INTERDEPENDENCE AND IMPACT ON COMMUNICATION - Karimberganova Shahnoza Muxammad qizi; Ruzmetova Diana Kamilovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Language and culture form intricate relationships as they influence each other and shape identity and communication among humans. This paper will analyze the interplay  between  culture  and  language  by  highlighting  how  values  determine expressions of culture and vice versa. It will also cover how language is linked to social transmission  of  norms  and  values  associated  with  cultures.  This  paper  will  also highlight the role of culture competence for effective intercultural communication and how education is integral to social awareness for culture. It will also cover how loss of languages affects culture because of globalization. It will thus conclude that effective interplay between culture and language is integral for successful communication and mutual social understanding among humans in this modern interrelated social world.